Insecticide Resistance of Aedes aegypti Linnaeus (Diptera: Culicidae) in the Northeast of Thailand - Sornpeng, Wasana; Pimsamarn, Supanee; Akksilp, Somsak (Journal of Health Science of Thailand, 2017)
Aedes aegypti Linnaeus is a carrier of dengue fever, which is a public health problem in the Northeast of Thailand. During epidemic, stresses were made on use of insecticides for control of the disease. A survey of chemicals used was carried out in eight provinces, namely Ubon Ratchathani, Si Sa Ket, Yasothon, Amnat Charoen, Mukdahan, Nakhon Phanom, Sakon Nakhon and Kalasin. The study indicated that one chemical used in the control of mosquito larvae was 1 % temephos. The most used chemical for control of adult mosquitoes by spraying was cypermethrin. From the study of the susceptibility of Ae. aegypti to chemically-impregnated paper using 0.05 % deltamethrin, 5 % malathion, and 1 % fenitrothion it was effective at a medium to high level. With regard to the susceptibility of Ae. aegypti to 0.75 % permethrin, the finding indicated that its effectiveness was at a low level. Based on the results of resistance ratio of Ae. aegypti comparing with susceptible strain, Ae. aegypti showed a resistance to deltamethrin and permethrin at a high level, with a resistance ratio of 10 fold greater. Regarding the resistance in all areas of Ae. aegypti to malathion and fenitrothion, the result was at a low to medium level. From a biochemical examination, the results demonstrated that monooxygenase and the esterase activity of Ae. aegypti had increased in all strains. Nevertheless, the glutathione-S-stransferase activity had increased in seven strains. Therefore, monooxygenase, esterase, and glutathione S-transferase activity were associated with mechanisms for creating pyrethroid-resistance in Ae. aegypti. Those were used for control of adult mosquitoes, which showed high resistance ratio to the chemicals in these areas. Consequently, if treatment using insecticides is still applied continuously, there is a possibility that those insects will become more resisting and, therefore hamper the control of mosquitoes in the future.